Abnormal psychology; : the problem of maladaptive behavior / Irwin G Sarason; Barbara R Sarason - Sarason, Irwin G.
Aims to provide students with a review of the field of abnormal psychology. In the 8th edition, the authors employ an interactional framework that incorporates personal and situational variables to examine how vulnerability and resilience influence the likelihood of mental disorders.